Reading the 21st Century World: Self-Assessment of Digital Media Literacy among Secondary School Students in Malaysia - Pandian, Ambigapathy; Baboo, Shanthi Balraj; Yi, Lim Jing (International Journal of Asian Social Science, 2020)
Students today participate in digital media cultures in numerous ways and it is important to consider their level of confidence in understanding their digital skills. The focus on digital media literacy is important to ensure that students have sufficient knowledge and skills to participate in society and in the economy as productive citizens. This study aimed to examine the digital media skills of Malaysian students in selected schools in Malaysia. The study presents the findings of a self-assessment tool, consisting of 10 core domains that was constructed to respond appropriately to the needs of students in secondary schools in Malaysia. The self-reporting by the students indicated that in general, they were quite self-assured about their capacities and many of them have rated their digital media skills at fairly high confidence levels. The findings suggest that many of students considered that they were competent in the areas of mobile, social and problem solving skills when working within digital platforms. However, the respondents deemed that the most challenging domain was creative as they felt less competent when it came to doing creative tasks using digital tools. By way of conclusion, this paper urges education authorities and schools to develop digital media literacy programmes that enhance students’ capacities in confronting challenges as well as exercising rights as active and responsible digital citizens.